(untitled) (Música Hodie, 2017)
The subject matter discussed in the text is a symphonic poem by Ferenc Kova? (KOVÁCS, 1948) titled “Ratna poema” (The War Poem) arranged for piano and tamburitza orchestra. The premiere performance of the piece by the pianist Sla?ana Mari? and The Grand Tamburitza Orchestra of Radio-Television of Vojvodina, conducted by F. Kova?, was held on 24th of May, 2011 in Novi Sad, Serbia. The main purpose of this research was to discuss this unique music piece in contemporary piano and tamburitza orchestra repertoire. Methodology was based on soft or research interview and analytical approach. The main conclusion was that, in general, this orchestral work with a solo piano, is a unique combination of memorable tunes, solid construction, and vivid orchestration. The analytical interpretations offered in this paper may be the first guidance for future interpretation or performance of the piece. Keywords: Kova? (Kovács) Ferenc; Musical analysis and performance; Piano Repertoire; Tamburitza Orchestra.